Song text of the Bashi - Merriam, Alan P. (International Library of African Music, 1954)
One hundred and twenty-one songs were recorded with the Bashi; eighty-nine of the texts contained sufficiently clear ideas for analysis. These songs are perforce “social” songs, that is, songs sung on social occasions as opposed to those of specialised application; thus, for example, songs in which natural or supernatural forces are petitioned are not included here. Rather, those songs sung or played at beer drinks, feasts, marriage celebrations and like events form the basis for this study, for these are the texts in which comment is made upon subjects of general interest to the people who sing them.
Keywords: Ethnomusicology; Songs; Bashi (African people); Gender Relations; African Music; Democratic Republic of the Congo; Belgian Congo; Music Manners; Music Customs